Pendampingan NIB dan Sertifikasi Halal Bagi UMKM di Desa Batukerbuy, Kecamatan Pasean - Firdauzi, Muhammad Ridlo; Putri, Dean Elviana; Rabbani, Bintang Cahya; Ariyani, Aminah Happy Moninthofa (Jumat Pertanian: Jurnal Pengabdian Masyarakat, 2024)
Batukerbuy Village is one of the areas in Pasean District, Pamekasan Regency. Batukerbuy Village is a village that has quite a large number of MSMEs and LMKM contributions to community welfare. However, the development of MSMEs in Batukerbuy Village is hampered by business legality permits and halal certificates. This is due to the lack of knowledge of MSME actors regarding the procedures for submitting business legality (NIB) and processing halal certification. Business legality and halal certificates are two important aspects that influence consumers' desires and trust in the type of product or business from MSMEs. Therefore, outreach and assistance were carried out to MSMEs in Batukerbuy Village regarding applying for business legality in the form of a Business Identification Number (NIB) and processing halal certificates. The strategies used in this service activity include discussion and coordination with the Village Apparatus and the hamlet head of Batukerbuy Village, socialization and assistance for MSME actors, assistance and creation of a NIB as a condition for applying for a halal certificate and mapping of MSMEs whose NIB has been issued to continue with halal certification. This mentoring program was welcomed enthusiastically by the community, especially business actors who intend to develop their businesses because the NIB and halal certification can help with promotions and gain more trust from consumers.